2010
DOI: 10.1345/aph.1p394
|View full text |Cite
|
Sign up to set email alerts
|

The Mandatory Residency Dilemma: Parallels to Historical Transitions in Pharmacy Education

Abstract: In parallel with the entry-level degree debate, consensus has yet to be reached among pharmacists and pharmacy organizations, but several have shown support for mandatory residency training for all pharmacists involved in direct patient care. Many questions have yet to be answered regarding the timeline, economics, and feasibility of such a mandate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…21 The reasoning behind these declarations stemmed from the 2004 CAPE educational outcomes, which described patient-centered care as an aspect of pharmaceutical care that all pharmacists must be able to provide in order to be competent practitioners. 22 ASHP-accredited PGY1 pharmacy residency programs are the focus of this article when discussing residencies as these are the most prevalent pharmacy residency opportunities at this time.…”
Section: Pharmacy Residency Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The reasoning behind these declarations stemmed from the 2004 CAPE educational outcomes, which described patient-centered care as an aspect of pharmaceutical care that all pharmacists must be able to provide in order to be competent practitioners. 22 ASHP-accredited PGY1 pharmacy residency programs are the focus of this article when discussing residencies as these are the most prevalent pharmacy residency opportunities at this time.…”
Section: Pharmacy Residency Programsmentioning
confidence: 99%
“…Compounding this issue is the decreasing availability of full-time positions after completion of residencies in some practice areas, decreasing the incentive for some pharmacy graduates to apply. 22 Despite the burdens of establishing and maintaining residencies, there are potential benefits for the hosting institution or organization. A retrospective cost-benefit analysis involving primary care and pharmacy practice residents at a Veterans Affairs (VA) hospital found that residents provided the VA with "in-house" methods for professional development through continuing education presentations, and an internal pool of qualified, trained candidates from which to select to fill clinical positions.…”
mentioning
confidence: 99%
“…and the revamped professional pharmacy curriculum are designed to adequately prepare graduates to provide direct patient care. 51 Thus, research into the appropriate education and training model for pharmacists providing direct patient care would be valuable.…”
Section: Pharmacy Practice Considerationsmentioning
confidence: 99%
“…51 For one, MTM services have not been broadly available to patients. Medicare prescription drug plans (PDPs) have been the primary source of demand for MTM services, but rigid eligibility requirements have resulted in only 10% of the Medicare patient population being eligible to receive these services, and many patients are being served through telephonic delivery methods implemented by the PDP.…”
Section: Pharmacy Practice Considerationsmentioning
confidence: 99%
“…1 A white paper for the American Association of Colleges of Pharmacy (AACP) Curricular Change Summit in 2009 by Jungnickel and colleagues proposed that curricula of the future foster the development of "leadership and advocacy." 2 Advocacy has been deemed an "essential competence" for pharmacists, a sentiment reflected in the Accreditation Council for Pharmacy Education (ACPE) accreditation standards for doctor of pharmacy programs.…”
Section: Introductionmentioning
confidence: 99%